Structural and mutational studies on an aldo‐keto reductase AKR5C3 from Gluconobacter oxydans. (23rd August 2014) - Liu, Xu; Wang, Chao; Zhang, Lujia; Yao, Zhiqiang; Cui, Dongbing; Wu, Liang; Lin, Jinping; Yuan, Yu‐Ren Adam; Wei, Dongzhi
Abstract An aldo‐keto reductase AKR5C3 from Gluconobacter oxydans (designated as Gox0644) is a useful enzyme with various substrates, including aldehydes, diacetyl, keto esters, and α‐ketocarbonyl compounds. The crystal structures of AKR5C3 in apoform in complex with NADPH and the D53A mutant (AKR5C3‐D53A) in complex with NADPH are presented herein. Structure comparison and site‐directed mutagenesis combined with biochemical kinetics analysis reveal that the conserved Asp53 in the AKR5C3 catalytic tetrad has a crucial role in securing active pocket conformation. The gain‐of‐function Asp53 to Ala mutation triggers conformational changes on the Trp30 and Trp191 side chains, improving NADPH affinity to AKR5C3, which helps increase catalytic efficiency. The highly conserved Trp30 and Trp191 residues interact with the nicotinamide moiety of NADPH and help form the NADPH‐binding pocket. The AKR5C3‐W30A and AKR5C3‐W191Y mutants show decreased activities, confirming that both residues facilitate catalysis. Residue Trp191 is in the loop structure, and the AKR5C3‐W191Y mutant does not react with benzaldehyde, which might also determine substrate recognition. Arg192, which is involved in the substrate binding, is another important residue. The introduction of R192G increases substrate‐binding affinity by improving hydrophobicity in the substrate‐binding pocket. These results not only supplement the AKRs superfamily with crystal structures but also provide useful information for understanding the catalytic properties of AKR5C3 and guiding further engineering of this enzyme.